A method for preparing a carbide coating on the surface of flake graphite by a molten salt method

By using the molten salt method to prepare the carbide plating layer on the surface of scale graphite, the problems of uneven thickness and inability to regulate the coating thickness in the prior art are solved, and a nano-scale carbide layer with high coverage and thin thickness are achieved, and the thermal conductivity of the composite material is improved.

CN118241197BActive Publication Date: 2025-04-01HARBIN INST OF TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410343625.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-03-25
Publication Date
2025-04-01
Estimated Expiration
2044-03-25

AI Technical Summary

Technical Problem

The existing methods of coating carbide coatings on the surface of scale graphite have problems such as thick carbide coatings, low coverage, uneven thickness, and inability to regulate thickness.

Method used

The carbide plating layer is prepared on the surface of the scale graphite by using the molten salt method. By mixing the scale graphite with metal powder in the liquid phase, the uniform distribution of metal on the surface of the scale graphite is achieved, and the salt particle size is refined by ball milling to ensure that the coating is high, the thickness is thin, and the distribution is evenly distributed.

Benefits of technology

A nano-scale carbide layer with high coverage, thin thickness and uniform distribution was prepared on the surface of scale graphite, solving the problems of uneven thickness and inability to regulate the coating, and improving the thermal conductivity of the composite material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118241197B_ABST
    Figure CN118241197B_ABST
Patent Text Reader

Abstract

A method for preparing a carbide coating on the surface of flake graphite by a molten salt method, and relates to a method for preparing a carbide coating on the surface of flake graphite. In order to solve the problems of the existing method of coating carbide coating on the surface of flake graphite, such as thick carbide coating, low coverage, uneven thickness, and uncontrollable thickness, the present invention wet mixes and controls the metal content and distribution of the coating on the surface of flake graphite, and reacts in a high-temperature molten salt environment, and finally prepares a nano-scale carbide layer with high coverage, thin thickness, uniform distribution, and adjustable morphology on the surface of flake graphite, and realizes full coverage of the coating on the flat surface of flake graphite and defects. The coating thickness can be adjusted by adjusting process parameters such as metal content, plating time, plating temperature, etc., so as to meet the needs of high thermal conductivity flake graphite reinforced metal matrix composite reinforcement.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for preparing a carbide coating on the surface of flake graphite. Background Art

[0002] With the continuous development of the field of electronic packaging, chips are gradually becoming integrated. The thermal management of chips is crucial to the performance release and service life of chips. Therefore, the market is looking for a new generation of materials that can be prepared on a large scale, are low-cost, have high thermal conductivity and thermal expansion coefficient that matches the chip. Flake graphite has a lamellar structure and has good high temperature resistance, electrical conductivity, thermal conductivity, wettability, plasticity and acid and alkali corrosion resistance. my country has abundant graphite resources, with reserves ranking first in the world, and the quality of graphite ore is very high, which is very advantageous in price. At present, flake graphite has been widely used as a reinforcement in metal-based composite materials. Because flake graphite has high thermal conductivity, metal-based composite materials with flake graphite as reinforcement have extremely high thermal conductivity potential.

[0003] Due to the poor chemical wettability between flake graphite and common metal matrix, the interface bonding formed is only mechanical bonding, so there is a problem of poor interface bonding. On the one hand, when the material as a whole bears a load, the flake graphite will be pulled out and fall off, causing the material structure to be damaged or even fail; on the other hand, the weak interface bonding will have an adverse effect on the heat transfer between the matrix and the reinforcement, resulting in a decrease in the overall thermal conductivity of the composite material. Studies have shown that plating modification on the surface of flake graphite can effectively improve the interface bonding of the composite material, thereby improving the thermal conductivity / comprehensive performance of the composite material. In addition, there is a theory that the thickness of the coating will also affect the thermal conductivity of the composite material. Relatively speaking, a thin carbide coating will have a low interface thermal resistance, which is beneficial to improving the thermal conductivity of the composite material. Therefore, how to prepare a thin and effective coating is the key to improving the thermal conductivity of the composite material, but at present, there are still problems in this regard, such as thick carbide coating, low coverage, uneven thickness, and uncontrollable thickness. Summary of the invention

[0004] In order to solve the problems of the existing method of coating a carbide coating on the surface of flake graphite, such as thick carbide coating, low coverage, uneven thickness, and uncontrollable thickness, the present invention proposes a method for preparing a carbide coating on the surface of flake graphite by a molten salt method.

[0005] The method for preparing a carbide coating on the surface of flake graphite by a molten salt method of the present invention is carried out according to the following steps:

[0006] 1. Weighing materials:

[0007] Weigh 20%-30% of flake graphite, 25% of sodium chloride, 25% of potassium chloride and the remainder of metal powder according to mass fraction;

[0008] The metal powder is chromium powder, titanium powder, tungsten powder or silicon powder;

[0009] The average particle size of the flake graphite is 250-2000 μm;

[0010] 2. Preparation of mixed powder of flake graphite and metal powder:

[0011] The flake graphite and the metal powder are mixed and added into anhydrous ethanol, and the mixture is stirred and mixed with the anhydrous ethanol as a medium, and then filtered to obtain a mixture of the flake graphite and the metal powder, and dried to obtain a mixed powder of the flake graphite and the metal powder;

[0012] The mass of the anhydrous ethanol is 1.5-3 times the total mass of the flake graphite and the metal powder;

[0013] The stirring and mixing is performed at a speed of 100-300 rpm for 10-24 hours;

[0014] 3. Preparation of mixed salt:

[0015] The sodium chloride and potassium chloride are ball-milled to obtain a fine and uniformly mixed salt;

[0016] The ball milling process is as follows: the ball-to-material ratio is (5-20):1, the rotation speed is 100-300rpm, and the time is 3-24h;

[0017] 4. Preparation of carbide coating with molten salt:

[0018] The mixed powder of the mixed salt, the flake graphite and the metal powder is placed in a mixer for stirring and mixing, the mixed powder is placed in an alumina crucible, and is kept at high temperature under a vacuum atmosphere or a protective atmosphere, and after the high temperature keeping is completed, the crucible is demoulded, placed in deionized water for heating and ultrasonic treatment, and then taken out and rinsed with deionized water and dried to obtain flake graphite with a carbide coating on the surface;

[0019] The stirring process has a rotation speed of 10-100 rpm and a time of 1-10 h;

[0020] The high temperature insulation process is as follows: temperature is 500-1600°C, heating rate is 1-100°C / min, insulation time is 10-360min, and cooling to room temperature;

[0021] The vacuum degree of the vacuum atmosphere is 1-10Pa;

[0022] The protective atmosphere is argon atmosphere, nitrogen atmosphere or helium atmosphere;

[0023] The heating temperature during the heating ultrasonic treatment is 60-90° C., and the treatment time is 0.5-1.5 h.

[0024] The present invention has the following beneficial effects:

[0025] 1. The method of preparing a carbide coating on the surface of flake graphite by the molten salt method adopted in the present invention is different from the method of introducing plating elements in the traditional molten salt plating method. The present invention mixes flake graphite with metal powder in the liquid phase, thereby achieving uniform distribution of metal on the surface of two-dimensional material flake graphite, and solving the problem that plating elements are difficult to be evenly distributed on the surface of flake graphite in a molten salt environment.

[0026] 2. The present invention wet mixes and controls the metal content and distribution of the coating on the surface of flake graphite, reacts in a high-temperature molten salt environment, and finally prepares a nano-scale carbide layer with high coverage, thin thickness, uniform distribution, and adjustable morphology on the surface of flake graphite, achieving full coverage of the coating on the flat surface of flake graphite and defects. The coating thickness can be adjusted by adjusting process parameters such as metal content, plating time, plating temperature, etc., thereby meeting the needs of high thermal conductivity flake graphite reinforced metal matrix composite reinforcement.

[0027] 3. The molten salt of the present invention is prepared by ball milling, which can eliminate the agglomeration in the salt and refine the salt particle size, so that the two salts are evenly mixed to meet the molten salt requirements.

[0028] 4. The nano-scale carbide coating on the surface of the flake graphite of the present invention has high purity and adjustable thickness. Different carbides can be plated on the surface of the flake graphite to meet different types of graphite modification requirements, greatly enriching the functionality and innovation of the modified graphite.

[0029] 5. The present invention adopts a low-speed mechanical mixing method which will not destroy the structure of flake graphite, thereby ensuring the functional integrity of graphite. The preparation process is simple, the equipment requirements are low, the preparation cost is low, and the single production volume is large. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 This is a SEM image of the chromium carbide plated on the surface of the flake graphite obtained in Example 1. DETAILED DESCRIPTION

[0031] The technical solution of the present invention is not limited to the specific implementation modes listed below, but also includes any reasonable combination of the specific implementation modes.

[0032] Specific implementation method 1: The method for preparing a carbide coating on the surface of flake graphite by a molten salt method in this implementation method is carried out according to the following steps:

[0033] 1. Weighing materials:

[0034] Weigh 20%-30% of flake graphite, 25% of sodium chloride, 25% of potassium chloride and the remainder of metal powder according to mass fraction;

[0035] The metal powder is chromium powder, titanium powder, tungsten powder or silicon powder;

[0036] The average particle size of the flake graphite is 250-2000 μm;

[0037] 2. Preparation of mixed powder of flake graphite and metal powder:

[0038] The flake graphite and the metal powder are mixed and added into anhydrous ethanol, and the mixture is stirred and mixed with the anhydrous ethanol as a medium, and then filtered to obtain a mixture of the flake graphite and the metal powder, and dried to obtain a mixed powder of the flake graphite and the metal powder;

[0039] The mass of the anhydrous ethanol is 1.5-3 times the total mass of the flake graphite and the metal powder;

[0040] The stirring and mixing is performed at a speed of 100-300 rpm for 10-24 hours;

[0041] 3. Preparation of mixed salt:

[0042] The sodium chloride and potassium chloride are ball-milled to obtain a fine and uniformly mixed salt;

[0043] The ball milling process is as follows: the ball-to-material ratio is (5-20):1, the rotation speed is 100-300rpm, and the time is 3-24h;

[0044] 4. Preparation of carbide coating with molten salt:

[0045] The mixed powder of the mixed salt, the flake graphite and the metal powder is placed in a mixer for stirring and mixing, the mixed powder is placed in an alumina crucible, and is kept at high temperature under a vacuum atmosphere or a protective atmosphere, and after the high temperature keeping is completed, the crucible is demoulded, placed in deionized water for heating and ultrasonic treatment, and then taken out and rinsed with deionized water and dried to obtain flake graphite with a carbide coating on the surface;

[0046] The stirring process has a rotation speed of 10-100 rpm and a time of 1-10 h;

[0047] The high temperature insulation process is as follows: temperature is 500-1600°C, heating rate is 1-100°C / min, insulation time is 10-360min, and cooling to room temperature;

[0048] The vacuum degree of the vacuum atmosphere is 1-10Pa;

[0049] The protective atmosphere is argon atmosphere, nitrogen atmosphere or helium atmosphere;

[0050] The heating temperature during the heating ultrasonic treatment is 60-90° C., and the treatment time is 0.5-1.5 h.

[0051] This embodiment has the following beneficial effects:

[0052] 1. The method of preparing a carbide coating on the surface of flake graphite by the molten salt method adopted in this embodiment is different from the method of introducing plating elements in the traditional molten salt plating method. This embodiment mixes flake graphite with metal powder in the liquid phase, thereby achieving uniform distribution of metal on the surface of two-dimensional material flake graphite, and solving the problem that plating elements are difficult to be evenly distributed on the surface of flake graphite in a molten salt environment.

[0053] 2. In this embodiment, the metal content and distribution of the coating on the surface of the flake graphite are controlled by wet mixing, and the reaction is carried out in a high-temperature molten salt environment. Finally, a nano-scale carbide layer with high coverage, thin thickness, uniform distribution, and adjustable morphology can be prepared on the surface of the flake graphite, achieving full coverage of the coating on the flat surface of the flake graphite and defects. The coating thickness can be adjusted by adjusting process parameters such as metal content, plating time, plating temperature, etc., thereby meeting the needs of high thermal conductivity flake graphite reinforced metal matrix composite reinforcement.

[0054] 3. The molten salt preparation in this embodiment can eliminate the agglomeration in the salt and refine the salt particle size through ball milling, so that the two salts are evenly mixed to meet the molten salt requirements.

[0055] 4. In this embodiment, the nano-scale carbide coating on the surface of flake graphite has high purity and adjustable thickness. Different carbides can be plated on the surface of flake graphite to meet different types of graphite modification requirements, greatly enriching the functionality and innovation of modified graphite.

[0056] 5. This embodiment adopts a low-speed mechanical mixing method which will not destroy the structure of flake graphite, thereby ensuring the functional integrity of graphite. The preparation process is simple, the equipment requirements are low, the preparation cost is low, and the single production volume is large.

[0057] Specific implementation method 2: This implementation method is different from specific implementation method 1 in that: the average particle size of the flake graphite in step 1 is 1000 μm.

[0058] Specific implementation method three: This implementation method is different from specific implementation methods one or two in that the mass of the anhydrous ethanol in step two is 1.5 times the total mass of the flake graphite and the metal powder.

[0059] Specific implementation method 4: This implementation method is different from any one of specific implementation methods 1 to 3 in that: the rotation speed of the stirring and mixing in step 2 is 250 rpm and the time is 10 hours.

[0060] Specific implementation method five: This implementation method is different from any one of specific implementation methods one to four in that: the ball milling process in step three is: the ball-to-material ratio is 20:1, the rotation speed is 250 rpm, and the time is 3 hours.

[0061] Specific implementation method 6: This implementation method is different from any one of specific implementation methods 1 to 5 in that: the rotation speed of the stirring mixing process in step 4 is 60 rpm and the time is 6 hours.

[0062] Specific implementation method seven: The difference between this implementation method and any one of specific implementation methods one to six is ​​that the high-temperature insulation process described in step four is: temperature is 900°C, heating rate is 10°C / min, insulation time is 10min, and cooling to room temperature.

[0063] Specific implementation eight: This implementation differs from any one of specific implementations one to seven in that: the vacuum degree of the vacuum atmosphere in step four is 1-10Pa.

[0064] Specific implementation method 9: This implementation method is different from any one of specific implementation methods 1 to 8 in that: the protective atmosphere in step 4 is an argon atmosphere, a nitrogen atmosphere or a helium atmosphere.

[0065] Specific embodiment ten: This embodiment differs from any one of specific embodiments one to nine in that: the heating temperature during the heating ultrasonic treatment in step four is 90° C., and the treatment time is 0.5 h.

[0066] Example 1

[0067] The method for preparing a carbide coating on the surface of flake graphite by a molten salt method in this embodiment is carried out according to the following steps:

[0068] 1. Weighing materials:

[0069] Weigh 30% of flake graphite, 25% of sodium chloride, 25% of potassium chloride and 20% of metal powder according to mass fraction;

[0070] The metal powder is chromium powder;

[0071] The average particle size of the flake graphite is 500 μm;

[0072] 2. Preparation of mixed powder of flake graphite and metal powder:

[0073] The flake graphite and the metal powder are mixed and added into anhydrous ethanol, and the mixture is stirred and mixed with the anhydrous ethanol as a medium, and then filtered to obtain a mixture of the flake graphite and the metal powder, and dried to obtain a mixed powder of the flake graphite and the metal powder;

[0074] The mass of the anhydrous ethanol is 1.5 times the total mass of the flake graphite and the metal powder;

[0075] The stirring and mixing was performed at a speed of 200 rpm for 10 h.

[0076] 3. Preparation of mixed salt:

[0077] The sodium chloride and potassium chloride are ball-milled to obtain a fine and uniformly mixed salt;

[0078] The ball milling process is as follows: the ball-to-material ratio is 5:1, the rotation speed is 100 rpm, and the time is 3 hours;

[0079] 4. Preparation of carbide coating with molten salt:

[0080] The mixed powder of the mixed salt, the flake graphite and the metal powder is placed in a mixer for stirring and mixing, the mixed powder is placed in an alumina crucible, and is kept at high temperature under a protective atmosphere, demolded after the high temperature keeping is completed, placed in deionized water for heating and ultrasonic treatment, and then taken out and rinsed with deionized water and dried to obtain flake graphite with a carbide coating on the surface;

[0081] The stirring process was performed at a speed of 50 rpm for 5 h.

[0082] The high temperature insulation process is as follows: temperature is 900°C, heating rate is 10°C / min, insulation time is 10min, and cooling to room temperature;

[0083] The protective atmosphere is an argon atmosphere;

[0084] The heating temperature during the heating ultrasonic treatment is 90° C. and the treatment time is 0.5 h.

[0085] Figure 1 This is a SEM image of the chromium carbide plated on the surface of the flake graphite obtained in Example 1. It can be seen that the surface of the flake graphite is completely coated with chromium carbide, with a coverage of 100% and a coating thickness of 30 to 40 nm.

[0086] Example 2

[0087] The method for preparing a carbide coating on the surface of flake graphite by a molten salt method in this embodiment is carried out according to the following steps:

[0088] 1. Weighing materials:

[0089] Weigh 25% of flake graphite, 25% of sodium chloride, 25% of potassium chloride and 25% of metal powder according to mass fraction;

[0090] The metal powder is chromium powder;

[0091] The average particle size of the flake graphite is 500 μm;

[0092] 2. Preparation of mixed powder of flake graphite and metal powder:

[0093] The flake graphite and the metal powder are mixed and added into anhydrous ethanol, and the mixture is stirred and mixed with the anhydrous ethanol as a medium, and then filtered to obtain a mixture of the flake graphite and the metal powder, and dried to obtain a mixed powder of the flake graphite and the metal powder;

[0094] The mass of the anhydrous ethanol is 1.5 times the total mass of the flake graphite and the metal powder;

[0095] The stirring and mixing was performed at a speed of 200 rpm for 15 h.

[0096] 3. Preparation of mixed salt:

[0097] The sodium chloride and potassium chloride are ball-milled to obtain a fine and uniformly mixed salt;

[0098] The ball milling process is as follows: the ball-to-material ratio is 10:1, the rotation speed is 150 rpm, and the time is 3 hours;

[0099] 4. Preparation of carbide coating with molten salt:

[0100] The mixed powder of the mixed salt, the flake graphite and the metal powder is placed in a mixer for stirring and mixing, the mixed powder is placed in an alumina crucible, and is kept at high temperature under a protective atmosphere, demolded after the high temperature keeping is completed, placed in deionized water for heating and ultrasonic treatment, and then taken out and rinsed with deionized water and dried to obtain flake graphite with a carbide coating on the surface;

[0101] The stirring process was performed at a speed of 80 rpm for 5 h.

[0102] The high temperature insulation process is as follows: temperature is 950°C, heating rate is 20°C / min, insulation time is 300min, and cooling to room temperature;

[0103] The protective atmosphere is a nitrogen atmosphere;

[0104] The heating temperature during the heating ultrasonic treatment is 90° C. and the treatment time is 1 hour.

[0105] The surface of the flake graphite obtained in Example 2 is completely coated with chromium carbide, with a coverage of 100% and a coating thickness of 50-70 nm.

[0106] Example 3

[0107] The method for preparing a carbide coating on the surface of flake graphite by a molten salt method in this embodiment is carried out according to the following steps:

[0108] 1. Weighing materials:

[0109] Weigh 20% flake graphite, 25% sodium chloride, 25% potassium chloride and 30% metal powder by mass;

[0110] The metal powder is chromium powder;

[0111] The average particle size of the flake graphite is 500 μm;

[0112] 2. Preparation of mixed powder of flake graphite and metal powder:

[0113] The flake graphite and the metal powder are mixed and added into anhydrous ethanol, and the mixture is stirred and mixed with the anhydrous ethanol as a medium, and then filtered to obtain a mixture of the flake graphite and the metal powder, and dried to obtain a mixed powder of the flake graphite and the metal powder;

[0114] The mass of the anhydrous ethanol is 1.5 times the total mass of the flake graphite and the metal powder;

[0115] The stirring and mixing was performed at a speed of 100 rpm for 24 h.

[0116] 3. Preparation of mixed salt:

[0117] The sodium chloride and potassium chloride are ball-milled to obtain a fine and uniformly mixed salt;

[0118] The ball milling process is as follows: the ball-to-material ratio is 20:1, the rotation speed is 250 rpm, and the time is 3 hours;

[0119] 4. Preparation of carbide coating with molten salt:

[0120] The mixed powder of the mixed salt, the flake graphite and the metal powder is placed in a mixer for stirring and mixing, the mixed powder is placed in an alumina crucible, and is kept at high temperature under a protective atmosphere, demolded after the high temperature keeping is completed, placed in deionized water for heating and ultrasonic treatment, and then taken out and rinsed with deionized water and dried to obtain flake graphite with a carbide coating on the surface;

[0121] The stirring process was performed at a speed of 60 rpm for 6 hours.

[0122] The high temperature insulation process is as follows: temperature is 1000°C, heating rate is 20°C / min, insulation time is 60min, and cooling to room temperature;

[0123] The protective atmosphere is a helium atmosphere;

[0124] The heating temperature during the heating ultrasonic treatment is 90° C. and the treatment time is 1.5 h.

[0125] The surface of the flake graphite obtained in Example 3 is completely coated with chromium carbide, with a coverage of 100% and a coating thickness of 60-70 nm.

Claims

1. A method for preparing a carbide coating on the surface of flake graphite by a molten salt method, characterized in that: The method for preparing a carbide coating on the surface of flake graphite by a molten salt method is carried out in the following steps:

1. Weighing materials: Weigh 30% flake graphite, 25% sodium chloride, 25% potassium chloride and 20% metal powder by mass fraction; The metal powder is chromium powder, titanium powder, tungsten powder or silicon powder; The average particle size of the flake graphite in step 1 is 500 μm; 2. Preparation of mixed powder of flake graphite and metal powder: The flake graphite and the metal powder are mixed and added into anhydrous ethanol, and the mixture is stirred and mixed with the anhydrous ethanol as a medium, and then filtered to obtain a mixture of the flake graphite and the metal powder, and dried to obtain a mixed powder of the flake graphite and the metal powder; The mass of the anhydrous ethanol is 1.5 times the total mass of the flake graphite and the metal powder; The stirring and mixing was performed at a speed of 200 rpm for 10 h.

3. Preparation of mixed salt: The sodium chloride and potassium chloride are ball-milled to obtain a fine and uniformly mixed salt; The ball milling process was as follows: ball-to-material ratio was 5:1, rotation speed was 100 rpm, and time was 3 h; 4. Preparation of carbide coating with molten salt: The mixed powder of the mixed salt, the flake graphite and the metal powder is placed in a mixer for stirring and mixing, the mixed powder is placed in an alumina crucible, and is kept at high temperature under a vacuum atmosphere or a protective atmosphere, demolded after the high temperature keeping is completed, placed in deionized water for heating and ultrasonic treatment, then taken out and rinsed with deionized water and dried to obtain flake graphite with a carbide coating on the surface, wherein the surface of the flake graphite is completely coated with chromium carbide, the coverage is 100%, and the coating thickness is 30-40nm; The stirring and mixing process was performed at a speed of 50 rpm and for 5 h; The high temperature insulation process is as follows: temperature is 900°C, heating rate is 10°C / min, insulation time is 10min, and cooling to room temperature; The vacuum degree of the vacuum atmosphere is 1-10Pa; The protective atmosphere is argon atmosphere, nitrogen atmosphere or helium atmosphere; The heating temperature during the heating ultrasonic treatment is 90° C. and the treatment time is 0.5 h.

Citation Information

Patent Citations

  • Metal-matrix composite material and preparation method thereof

    CN105861866A

  • Method for preparing silicon carbide coated graphite through molten salt isolation

    CN112125686A